The Use of Nucleosome Substrates Improves Binding of SAM Analogs to SETD8. (September 2016) - Strelow, John M.; Xiao, Min; Cavitt, Rachel N.; Fite, Nathan C.; Margolis, Brandon J.; Park, Kyu-Jin
SETD8 is the methyltransferase responsible for monomethylation of lysine at position 20 of the N-terminus of histone H4 (H4K20). This activity has been implicated in both DNA damage and cell cycle progression. Existing biochemical assays have utilized truncated enzymes containing the SET domain of SETD8 and peptide substrates. In this report, we present the development of a mechanistically balanced biochemical assay using full-length SETD8 and a recombinant nucleosome substrate. This improves the binding of SAM, SAH, and sinefungin by up to 10, 000-fold. A small collection of inhibitors structurally related to SAM were screened and 40 compounds were identified that only inhibit SETD8 when a nucleosome substrate is used.